Between Distance and Obligation: Spousal Maintenance in Long-Distance Muslim Marriages in Sukowidi Village under Islamic Family Law - Bagus Tinard Nugroho; Muhammad Harir Muzakki (Yayasan Abdurrauf Cendekia Nusantara, 2025)
In the context of modern life, challenges in fulfilling financial obligations often arise when couples are in a long-distance marriage. This occurs because the husband or wife leaves the city to earn a living or improve the family's economic situation. This article will discuss the efforts of husbands and wives in long-distance marriages to provide for their families and the implications of long-distance marriages on the provision of livelihoods for husbands and wives in Sukowidi Village, Kartoharjo District, Magetan Regency. This research is field research using data collection techniques, interviews, observation, and documentation. The reality in the Sukowidi community in Kartoharjo Subdistrict is that many husbands work outside the Magetan area. To answer the research questions, the researcher interviewed four families. The results of the study show that the majority of couples are able to fulfill their material needs (clothing, food, shelter), and confirm that distance does not hinder the fulfillment of needs as long as both parties have responsibility and commitment to each other. Success in fulfilling the husband's financial obligations to his wife is highly dependent on open communication, fair division of roles, and efforts to maintain emotional and spiritual needs. Long-distance marriage has significant implications for the psychological, emotional, and communication aspects of the family. [Dalam konteks kehidupan modern, tantangan pemenuhan nafkah sering muncul ketika pasangan harus menjalani pernikahan jarak jauh. Hal ini terjadi karena suami atau istri pergi ke luar kota untuk mencari nafkah atau memperbaiki perekonomian keluarga. Artikel ini akan membahas usaha suami istri pernikahan jarak jauh dalam pemenuhan nafkah dan bagaimana implikasi pernikahan jarak jauh dalam pemenuhan nafkah suami istri di Desa Sukowidi, Kecamatan Kartoharjo, Kabupaten Magetan. Penelitian ini merupakan penelitian field Research (Penelitian Lapangan) dengan teknik pengumpulan data, wawancara, observasi, dan dokumentasi. Realitas yang terjadi pada masyarakat Sukowidi Kecamatan Kartoharjo banyak suami yang bekerka di luar wilayah Magetan. Untuk menjawab masalah penelitian, peneliti mewancarai emapat keluarga. Hasil penelitian menunjukkan bahwa mayoritas pasangan dapat memenuhi nafkah lahir (sandang, pangan, papan), dan menegaskan bahwa jarak tidak menghambat pemenuhan nafkah selama keduanya memiliki tanggung jawab, komitmen antar pasangan. Keberhasilan dalam pemenuhan nafkah suami kepada istri sangat bergantung pada komunikasi yang terbuka, pembagian peran yang adil, serta upaya menjaga kebutuhan batin dan spiritual. Pernikahan jarak jauh membawa implikasi signifikan pada aspek psikologis, emosional, dan komunikasi dalam keluarga.]